Lithuanian National Identity: the Problem of the Relation between Ethnicity and Confessionality in the Interwar Period in Lithuanian Republic (1918-1940) - Trimakas, Ramūnas (Sociologija. Mintis ir veiksmas, 1999)
The aim of the article is to discuss the formation of Lithuanian national identity in the interwar period (1918-1940). The article analyzes the changing relationship between ethnic and religious aspects of Lithuanian identity and considers a thesis of change of Lithuanian self-unerstanding from ethnic-confessional to national-civic. Drawing on Smith, the author argues that the interwar years might be understood as a period of transition which delineates the two dimensions of Lithuanian identity neither of which becomes dominant in the period: the ethnic-confessional and the national-civic.